Continuing education of academic women in STEM: perspectives on mentoring and professional roles - García-Silva, Erika; Perez-Suarez, Sonia; Zavala-Parrales, Ana; Meléndez-Anzures, Frank E.; Dominguez, Angeles (Frontiers in Education, 2025)
Despite ongoing efforts towards gender equity, the gender gap in STEM (Science, Technology, Engineering, and Mathematics) remains significant today. This article explores the motivations and perceptions of women in different professional roles within STEM fields regarding the importance of mentoring in fostering interest and participation in STEM careers, thus contributing to continuing engineering education. Based on qualitative data from 19 semi-structured interviews with women in managerial, research, teaching, and external academic and professional roles, the study delves into their motivations for pursuing STEM careers, their interest in promoting diversity, and the role of mentoring in supporting their professional development. The thematic analysis results are grouped into a hierarchical structure comprising one meta-theme, four primary, and six subthemes. The participants emphasized that their primary motivation for STEM involvement was contributing to society and promoting economic growth. Additionally, they advocated for greater diversity and challenged traditional gender roles in these areas. The participants highlighted the importance of closing the gender gap and recognizing the capabilities and new perspectives that women brought. Although these women faced obstacles such as glass ceilings, having a mentorship opportunity was identified as a critical tool for women’s empowerment and training. The insights contribute to advancing strategies for promoting gender equity and diversity in STEM fields, with implications for researchers, universities, and organizations seeking to support women’s participation and advancement in STEM careers. Further research is recommended to explore the perspectives of women in other roles and the effectiveness of mentoring programs in fostering gender diversity in STEM.